Linking large‐scale climate variability with Arctica islandica shell growth and geochemistry in northern Norway. (31st December 2015) - Mette, Madelyn J.; Wanamaker, Alan D.; Carroll, Michael L.; Ambrose, William G.; Retelle, Michael J.
Abstract: The lack of high resolution, geographically diverse proxy records from the marine realm limits our understanding of climate dynamics in the North Atlantic Ocean and Arctic during recent centuries. We investigate the impact of large‐scale climate variability on the marine bivalve, Arctica islandica, (Linnaeus 1767) from northern Norway (71°N). We evaluate the use of annual shell growth and geochemical records as proxies for North Atlantic and Arctic climate variability over centennial scales by developing a continuous, 113‐yr master shell growth chronology and an oxygen isotope record (δ 18 O) from live caught shell material. A relatively strong inverse relationship is observed between both the shell growth and isotopic proxies and large‐scale North Atlantic sea surface temperatures in modern times ( r  = −0.54 to −0.90; p  < 0.05). This relationship is strengthened when using a combined shell growth/oxygen isotope Multiproxy Index ( r  = −0.72 to −0.90; p <0.01). The regional spatial pattern of correlation resembles that of the North Atlantic Current as it bifurcates around 55°N, indicating that large‐scale ocean surface current dynamics play an important role in regulating local ecosystem processes and thus shell growth in northern Norway. A combined proxy index created using multiple linear regression exhibits a relatively strong and time‐stable relationship with the Atlantic Multidecadal Oscillation (AMO; r  = −0.622; p  < 0.001) since AD 1900. Variability in the relationship between the shell based records and the North Atlantic Oscillation coincide with variations in the AMO index, suggesting a complex relationship between atmospheric forcing on hydrographic variability and ecosystem dynamics in northern Norway.